String flash-boiling in gasoline direct injection simulations with transient needle motion. (December 2016) - Baldwin, E.T.; Grover, R.O.; Parrish, S.E.; Duke, D.J.; Matusik, K.E.; Powell, C.F.; Kastengren, A.L.; Schmidt, D.P.
Highlights: A CFD study of multiphase GDI internal flow and near-field spray is described. Excellent agreement to experimental ROI is achieved with transient needle motion. Qualitative agreement to experimental imaging in the near-field is shown. Complex internal nozzle flow is shown to influence ROI and spray angle. Unsteady vortices cause string flash-boiling and expansion of the near-field spray. Abstract: A computational study was performed to investigate the influence of transient needle motion on gasoline direct injection (GDI) internal nozzle flow and near-field sprays. Simulations were conducted with a compressible Eulerian flow solver modeling liquid, vapor, and non-condensable gas phases with a diffuse interface. Variable rate generation and condensation of fuel vapor were captured using the homogeneous relaxation model (HRM). The non-flashing (spray G) and flashing (spray G2) conditions specified by the Engine Combustion Network were modeled using the nominal spray G nozzle geometry. Transient needle lift and wobble were based upon ensemble averaged X-ray imaging preformed at Argonne National Lab. The minimum needle lift simulated was 5 µm and dynamic mesh motion was achieved with Laplacian smoothing. The results were qualitatively validated against experimental imaging and the experimental rate of injection profile was captured accurately using pressure boundary conditions and needle motion to actuate the injection. Low needle lift is shown to result in vapor generation near the injector seat. Finally, the internal injector flow is shown to be highly complex, containing many transient and interacting vortices which result in perturbations in the spray angle and fluctuations in the mass flux. This complex internal flow also results in intermittent string flash-boiling when a strong vortex is injected and the resulting swirling spray contains a thermal non-equilibrium vapor core.